Volume 2A: Turbomachinery 2015
DOI: 10.1115/gt2015-42133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonuniform Tip Clearance on Fan Performance and Flow Field

Abstract: Nonuniform tip clearance, caused by the deformation of the casing (casing ovalization), exists in all fans to some extent. However, description of the flow behavior with this kind of nonuniform clearance is seldom given in the open literature. In this paper, both steady and unsteady calculations are performed to study the influence of the nonuniform clearance on fan performance and flow field. The investigation method is based on three dimensional RANS equations, carried out by the ANSYS CFX fluid solver. A ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In the analysis presented here, the standard k-" turbulence model was used for obtaining the turbulent viscosity. 32 The same numerical solver was used in past years 33 and has been validated with experiments. 16 The computational domain is shown in Figure 4.…”
Section: Methodsmentioning
confidence: 99%
“…In the analysis presented here, the standard k-" turbulence model was used for obtaining the turbulent viscosity. 32 The same numerical solver was used in past years 33 and has been validated with experiments. 16 The computational domain is shown in Figure 4.…”
Section: Methodsmentioning
confidence: 99%
“…The result is quite different from conclusions obtained by previous studies. Most of the researches on nonuniform tip clearance concluded that it led to performance degradation 6,8,15 or had little effect on compressor performance. 911 Further analysis is carried out below to interpret the performance improvement of the non-axisymmetric case.…”
Section: Effect Of Non-axisymmetric Clearance On Overall Performancementioning
confidence: 99%
“…In an aero-engine where tip clearance size and eccentricity change during each flight cycle and over the life of the compressor, 12 the redistribution of flow massively influences stall inception during throttling, 13,14 and the stall will occur in nonuniform clearance configurations once the minimum mass flow reaches to the local stall mass flow. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the circumferential nonuniformity of tip clearance has also been investigated. 25 According to the research of Chen et al, 26 the overall performance and flow structures are affected by two factors: clearance nonuniformity and average clearance level. There is a clear decreasing trend of the fan performance and stall margin with the increase of these two factors.…”
Section: Introductionmentioning
confidence: 99%